The Impact of Public Agricultural Spending on Foreign Direct Investment Inflows in Agriculture in South Africa: An ARDL Analysis - Mbiakop, William Djamfa; Khobai, Hlalefang; Fani, Djomo Choumbou Raoul (International Journal of Economics and Financial Issues, 2023)
Since the transformation of South African agriculture post-apartheid, public agricultural spending and foreign direct investment in agriculture were regarded as predominantly essential for the development of agriculture sector. However, many authors still argue whether public agriculture spending should be complemented by foreign direct investment inflows in agriculture or vice versa. Thus, the key focus of this paper is to investigate the impact of public agricultural spending on foreign direct investment inflows in agriculture in South Africa over the period 1991-2019. The Autoregressive distributed lag(ARDL) Bounds test and Granger causality were used to investigate both short run and long-run impact of public agricultural spending on foreign direct investment inflows in agriculture. The results of the long run model show that agriculture production has a positive and significant impact on foreign direct investment. However, public spending in agriculture has a negative and significant influence on the foreign direct investment inflows in agriculture. In addition, Granger causality results show causality flowing from public agriculture spending, net export and inflation to foreign direct investment inflows in agriculture. Hence, it is recommended that policymakers should take practical steps towards total eradication of misallocation and squandering of the available funds and redirected toward bridging infrastructural deficits, land restitution to promote foreign direct investment inflows the development of agriculture.